Felipe Carlos Manuel Paisán Adan - Salazar Cueto, Carlos E.; Rodríguez Acosta, Regino; Monteagudo Canto, Alina; González García, Luzimín (Archivo Médico Camagüey, 2015)
Felipe Carlos Manuel Paisán Adan